2014
DOI: 10.5007/1980-0037.2014v16n3p345
|View full text |Cite
|
Sign up to set email alerts
|

Prática de caminhada no lazer e no deslocamento e associação com fatores socioeconômicos e ambiente percebido em adultos

Abstract: -This study aimed to analyze the association between walking for leisure and commuting and the perceived environment in adults living in Rio Claro, São Paulo, Brazil. A cross-sectional household-based study was conducted with 470 adults (45.7±17.8 years). Subjects responded to the International Physical Activity Questionnaire (long version) and to an adapted version of the Neighborhood Environmental Walkability Scale, which was used to evaluate the perceived built and social environments. Data analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
2
4
0
1
Order By: Relevance
“…In this study we found that more men than women walk 150 minutes or more a week. Similar results were found when other domains of physical activity are included 43,44 . Despite the dif-ference in the prevalence of walking among men and women in Brazil, there are few studies that incorporate discussions of gender and the social constructs that may be involved in these differences.…”
Section: Discussionsupporting
confidence: 84%
“…In this study we found that more men than women walk 150 minutes or more a week. Similar results were found when other domains of physical activity are included 43,44 . Despite the dif-ference in the prevalence of walking among men and women in Brazil, there are few studies that incorporate discussions of gender and the social constructs that may be involved in these differences.…”
Section: Discussionsupporting
confidence: 84%
“…Já em relação à atividade física no lazer de predominância aeróbia, como a corrida em locais abertos, observou-se que essa foi uma das principais práticas entre as universitárias. A caminhada [27][28][29] e corrida 27 foram relatadas em outros estudos como sendo as principais modalidades praticadas por mulheres. As práticas aeróbias realizadas no lazer, como a caminhada, podem possibilitar menores riscos de fraturas 30 e a obtenção de benefícios em níveis metabólicos e musculares de mulheres na meia idade e idosas, deste modo a prática em idades iniciais poderá favorecer o envelhecimento saudável, além disso, representam atividades de maior acessibilidade, que assim oportunizam a realização de forma regular e com maior autonomia das praticantes.…”
Section: Discussionunclassified
“…Walking prevalence, as the main physical activity in leisure time and in commuting to work, was considered low. In Brazil, there are few studies that have specifically assessed physical activity in adult workers simultaneously in both domains (Humpel et al, 2004;Teixeira, Nakamura & Kokubun, 2014). This result can be partly explained by various environmental factors such as the rapid growth of cities, which could result in diminished opportunities for performing physical activity during leisure time, as well as greater difficulties for active commuting (Robroek et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the differences in sociodemographic factors associated with walking during leisure time and commuting to work is very important for the development of public policies that helping to increase this behavior in society (Thomaz, Costa, Silva & Hallal, 2010), aiming to a more active and healthy lifestyle. In addition, it should be highlighted that women and men have different attitudes towards active behavior, especially walking (Hallal et al, 2005;Kruger et al, 2008), and that there are few studies addressing simultaneously walking during leisure time and commuting to work (Humpel, Owen, Iverson, Leslie, & Bauman, 2004;Teixeira, Nakamura & Kokubun, 2014;. Therefore, the objective of the study was to identify the prevalence of walking for leisure and for commuting R.R.…”
Section: Introductionmentioning
confidence: 99%